The Role of a Mission Organization in Building a Sustainable Government Hospital in Southern Ethiopia - Bernt Lindtjørn (Health for All Nations, 2020)
In 1950, the Norwegian Lutheran Mission (NLM) began holistic mission work, including health work in Yirga Alem in Sidama in Southern Ethiopia. The hospital, which had served as a military hospital during the Italian war (1936-41), became a mission hospital. This paper presents some historical developments of a government hospital managed by a mission organization, the story of its medical work, and how the NLM functioned under varying political regimes and societal environments in Southern Ethiopia. At the same time, societal changes occurring in Norway with the weakening of mission organizations and the Norwegian government's policy that influenced external financial support for the hospital are presented and discussed. The key message of the paper is that it is possible under challenging external politics for a mission organization to collaborate with government entities even with difficult regimes. In the area of Yirga Alem Hospital, this was done without compromising the basics of mission, but rather readjusting comparative strategies while ensuring sustainability and local ownership. The uniqueness of this work is that it explores a mission, i.e., the NLM, which developed health work within the context of a nationally owned health service. Moreover, this fruitful collaboration persists until this day and previous missionaries still work to strengthen public health programs that target such major areas as tuberculosis and HIV control, maternal health, childcare, and nutrition.